Portrayals of the Holocaust in English history textbooks, 1991–2016: continuities, challenges and concerns. Issue 3 (3rd July 2017) - Foster, Stuart; Karayianni, Eleni
ABSTRACT: This study examines portrayals of the Holocaust in a sample of 21 secondary school history textbooks published in England between 1991 and 2016. Evaluated against internationally recognized criteria and guidelines, the content of most textbooks proved very problematic. Typically, textbooks failed to provide clear chronological and geographical frameworks and adopted simplistic Hitler-centric, perpetrator-oriented narratives. Furthermore, textbooks paid limited attention to pre-war Jewish life, the roots of antisemitism, the complicity of local populations and collaborationist regimes, and the impact of the Holocaust on people across Europe. Based on these critical findings, the article concludes by offering initial recommendations for textbook improvement.